Utilization of preconception care and associated factors among pregnant mothers in Fiche Town, Central Ethiopia: a community-based cross-sectional study 2021 - Fetena, Negash; Negash, Abraham; Kebede, Alemi; Sertsu, Addisu; Nega, Addisu; Nigussie, Kabtamu; Lami, Magarsa; Yadeta, Elias; Dereje, Jerman; Tamire, Aklilu; Tolessa, Fikadu; Tadele, Afework (Frontiers in Global Women's Health, 2023)
Introduction Preconception care is an important preventive intervention for adverse pregnancy outcomes. It is recognized as a strategy to optimize women's health and pregnancy outcomes in Western countries. However, preconception care is underutilized in sub-Saharan Africa, like Ethiopia, where maternal mortality is high. Evidence is scarce in the study area about the prevalence and factors associated with preconception care utilization. Therefore this study aimed to assess the proportion of preconception care utilization and associated factors among pregnant mothers in Fiche town, central Ethiopia, 2021. Method A community-based cross-sectional study was done from May 10 to June 25, 2021. A systematic random sample technique was used to choose 393 pregnant women for the study. A structured, pre-tested, interviewer-administered questionnaire was used to collect data. The data were entered into Epi Data version 3.1 and then exported into SPSS version 25 for analysis. A Bivariable and multivariable logistic regression analysis was used to check for the association. Odds ratio along with 95% was used to describe the association. Finally, a significant association was declared at a p-value less than 0.05. Results 388 respondents participated in this study, making the response rate 98.7%. Of total study participants only 84 (21.6%; 95% CI, 18, 25.8) utilized preconception care. The study found that diploma or higher level of education (AOR = 3.47, 95% CI: 1.27, 9.53), psychological and financial support from a partner (AOR = 3.86, 95% CI: 2.1, 7.10), joint discussion and plan with a partner (AOR = 3.32, 95% CI: 1.55, 7.13), history of chronic disease (AOR = 3.47, 95% CI: 1.67, 7.25), and good knowledge about preconception care (AOR = 2.42, 95% CI: 1.34, 4.38) were significantly associated with preconception care utilization. Conclusions Overall, less than a quarter of the pregnant mothers utilized preconception care, indicating that awareness is very low. Pregnant mothers who have a higher educational level, have good communication and support from their partners, have chronic health problems, and have good knowledge about preconception care were more likely to utilize the service. Preconception care is a better opportunity to intervene and maintain the mother in the continuum of care.